(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article deals with the pragmatic potential of lingu-stylistic facilities, noticed in the P. Zagrebel’nyi’s novel «Evil». The list of author’s stylestem, the communicative and pragmatic meanings, the criteria of their holistic values are determined. The functionally-classification features of stylistic figures and their semantic and pragmatic marking are described.